New Zealand Bodotriidae (Crustacea: Cumacea) - Gerken, Sarah (Zootaxa, 2013)
The cumacean fauna of New Zealandhas been little studied, and recent collections on the Chatham Rise and Challenger Plateau have yielded many new species and new genera of Cumacea. A recent manuscript on the New ZealandNannast-acidae (Gerken 2012) increased the described New Zealandfauna by 66%. Within the Bodotriidae, 6 new species were discovered. The new species Apocuma chathamensis n. sp., A. sculpta n. sp., Bathycuma dayae n. sp., Cyclaspis petrescui n. sp., C. hayeae n. sp. and C. zealandiaensis n. sp. are described, and keys to all New Zealand Bodotriidae are provided.